2014
DOI: 10.5114/fn.2014.43791
|View full text |Cite
|
Sign up to set email alerts
|

Original article Dendritic and spinal alterations of neurons from Edinger-Westphal nucleus in Alzheimer’s disease

Abstract: A b s t r a c t Alzheimer's disease (AD) is a heterogeneous neurodegenerative disorder, causing a progressive decline of intellectual faculties, impairment of behavior and social performance, and impairment of speech eloquence, associated with various neurological manifestations based on a variable neuropathological background. Edinger-Westphal nucleus is a selective target of Alzheimer pathology early in the course of the disease. We attempted to determine the morphological alterations of the dendrites and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Reduced dendritic arborization, diminished spine numbers, synaptic loss, and neuronal death have been widely reported in AD patients and in animal models of this disease [17, 18, 47, 7882]. Loss of dendritic complexity and reduced spine densities are also prominent features of AD and correlate significantly with cognitive decline [16].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced dendritic arborization, diminished spine numbers, synaptic loss, and neuronal death have been widely reported in AD patients and in animal models of this disease [17, 18, 47, 7882]. Loss of dendritic complexity and reduced spine densities are also prominent features of AD and correlate significantly with cognitive decline [16].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that the dysfunction of synapses and dendritic spines precedes neuronal dysfunction and death during AD-induced neurodegeneration (Chabrier et al 2014;Mavroudis et al 2014). These hypotheses are supported by evidence from studies examining various postmortem tissue samples obtained from AD patients, in which a loss of dendritic spines was clearly detected in the hippocampus and other brain areas associated with AD pathology (Knobloch and Mansuy 2008).…”
Section: Discussionmentioning
confidence: 89%
“…; Mavroudis et al . ). These hypotheses are supported by evidence from studies examining various postmortem tissue samples obtained from AD patients, in which a loss of dendritic spines was clearly detected in the hippocampus and other brain areas associated with AD pathology (Knobloch and Mansuy ).…”
Section: Discussionmentioning
confidence: 97%
“…Dendritic spines are tiny protrusions of dendrites that are essential for excitatory synaptic transmission [6,7,22]. AD brains show a marked reduction in synaptic density and a loss of dendritic spines in the cortex and the hippocampus [9,31]. Synaptic impairment is likely to be the major contributor to memory loss in AD [23,41].…”
Section: Discussionmentioning
confidence: 99%